2007
DOI: 10.1089/neu.2006.0035
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable Prognostic Analysis in Traumatic Brain Injury: Results from The IMPACT Study

Abstract: We studied the prognostic value of a wide range of conventional and novel prognostic factors on admission after traumatic brain injury (TBI) using both univariate and multivariable analysis. The outcome measure was Glasgow Outcome Scale at 6 months after injury. Individual patient data were available on a cohort of 8686 patients drawn from eight randomized controlled trials and three observational studies. The most powerful independent prognostic variables were age, Glasgow Coma Scale (GCS) motor score, pupil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
378
5
29

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 555 publications
(442 citation statements)
references
References 23 publications
30
378
5
29
Order By: Relevance
“…Nonneurological organ dysfunction is an important predictor 66 Early physiological derangements are known to be associated with worse outcomes, and their timely correction could influence recovery. [67][68][69] Consistent with this notion, one randomized controlled trial demonstrated that pre-hospital rapid sequence intubation (RSI) by paramedics increased the proportion of TBI patients with a favourable neurological recovery. 14 Pre-hospital RSI was routine practice in Southern Alberta even before the time period assessed in this study.…”
Section: Discussionmentioning
confidence: 93%
“…Nonneurological organ dysfunction is an important predictor 66 Early physiological derangements are known to be associated with worse outcomes, and their timely correction could influence recovery. [67][68][69] Consistent with this notion, one randomized controlled trial demonstrated that pre-hospital rapid sequence intubation (RSI) by paramedics increased the proportion of TBI patients with a favourable neurological recovery. 14 Pre-hospital RSI was routine practice in Southern Alberta even before the time period assessed in this study.…”
Section: Discussionmentioning
confidence: 93%
“…1 The most extensively validated scoring system for TBI outcome is the International Mission for Prognosis and Analysis of Clinical Trials (IMPACT) score. 2 It is based on a multivariate model that combines clinical, biochemical, and computed tomography (CT) variables at admission to provide a probabilistic estimate of the outcome at 6 months. The IMPACT score is accurate in predicting outcomes in populations of patients with moderate and severe TBI but has limited utility in making decisions regarding any individual patient.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of PVS at six months after onset may be irrelevant to age and gender in the included studies, but no study has reported the effect of age and sex on the prevalence of PVS. Age probably has an impact on the outcome of TBI because it is an important factor in some models predicting the prognosis after TBI (Boyd, Tolson, & Copes, 1987;Murray et al, 2007;Perel et al, 2008) Thus, the reason for the negative result may be that the number of included studies is limited, and most of the studies have a similar mean age (27-49.3 years) and gender composition (0.698-0.818). These factors make it less likely that a significant result can be drawn from the multiple meta-regression analysis.…”
Section: Age and Sexmentioning
confidence: 99%